INTERVENSI MILITER TURKI TERHADAP WILAYAH KEDAULATAN SURIAH TAHUN 2016 – 2019 - Zikri, Andi Ahmad Khairullah; Saeri, M. (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This paper aims to analyze the Turkish military intervention against the Syrian sovereign territory in 2016 - 2019. The Syrian crisis has directed threats indirectly to Turkey's presence of Kurdish groups on the border. The Kurdistan Workers' Party or PKK activity in Syria. Syria made the PKK affiliated with the Syrian Kurdish group, the Democratic Union Party or PYD a particularly important actor in the northern region of the state during the crisis. In the midst of instability due to the army's conflict in Syria, Turkey believes that the political nature and military strength of the PKK & PYD can harm its domestic security or stability. Now the PKK is still a separate region or autonomy for the Kurdish southeast.The perspective used in this research is the perspective of Neo-Realism by Kenneth Waltz, as well as the analysis of the nation-state level. This study uses the theory of national security and the concept of intervention that explains Turkey's relationship with threats to security or stability whose approach is a vital national interest.This research shows that the threat of the Syrian Kurdish PKK & PYD encourages Turkey to intervene in Syria's sovereign territory. The first Turkish military intervention was carried out in 2016 under the name Operation Euphrates Shield, the second in 2018 Operation Olive Branch, and the third in 2019 Operation Peace Spring. The Turkish military intervention aims to weaken and limit the political and military movements of the Kurdish group in northern Syria, create a safe zone (safe zone) on the Syrian border for the Syrian refugee community in Turkey, and integrate Syrian territory, in addition to weakening the influence of the Kurdish PKK & PYD and creating a safe zone for Syrian refugees, Turkey also has Economic interests and Political interests in the Syrian Conflict.Â Keywords: Syrian, Turkey, Threat, PKK & PYD, National Security, Military Operations